Swimmer - Gill, Shelley; Cartwright, Shannon (Homer, Alaska : Paws IV Pub., 1995)
Swimmer, the Chinook salmon, journeys over 10,000 miles to complete her life cycle, while Katya, the native Alaskan girl, comes of age in her small village along the coast.
Keywords: Chinook salmon -- Juvenile fiction; Chinook salmon -- Fiction; Salmon -- Fiction; Alaska -- Fiction